Advanced editing of the nuclear and plastid genomes in plants. (August 2018) - Piatek, Agnieszka A.; Lenaghan, Scott C.; Neal Stewart, C.
Highlights: Site-specific nucleases are key enabling tools for plant genome editing for endowment of new agronomically important traits in crop plants. Homologous recombination mediates the "scarless" insertion of transgenes for gene correction or gene addition and/or gene stacking. The prokaryotic nature of plastid molecular genetics provides unique opportunities for complex metabolic pathway engineering. Grand challenge traits such as photosynthesis and nitrogen fixation are important targets. Synthetic plastomes will enable facile and seamless insertion of transgenes and complex metabolic pathways. Abstract: Genome editing is a powerful suite of technologies utilized in basic and applied plant research. Both nuclear and plastid genomes have been genetically engineered to alter traits in plants. While the most frequent molecular outcome of gene editing has been knockouts resulting in a simple deletion of an endogenous protein of interest from the host's proteome, new genes have been added to plant genomes and, in several instances, the sequence of endogenous genes have been targeted for a few coding changes. Targeted plant characteristics for genome editing range from single gene targets for agronomic input traits to metabolic pathways to endow novel plant function. In this paper, we review the fundamental approaches to editing nuclear and plastid genomes in plants with an emphasis on those utilizing synthetic biology. The differences between the eukaryotic-type nuclear genome and the prokaryotic-type plastid genome (plastome) in plants has profound consequences in the approaches employed to transform, edit, select transformants, and indeed, nearly all aspects of genetic engineering procedures. Thus, we will discuss the two genomes targeted for editing in plants, the toolbox used to make edits, along with strategies for future editing approaches to transform crop production and sustainability. While CRISPR/Cas9 is the current method of choice in editing nuclear genomes, the plastome is typically edited using homologous recombination approaches. A particularly promising synthetic biology approach is to replace the endogenous plastome with a 'synplastome' that is computationally designed, and synthesized and assembled in the lab, then installed into chloroplasts. The editing strategies, transformation methods, characteristics of the novel plant also affect how the genetically engineered plant may be governed and regulated. Each of these components and final products of gene editing affect the future of biotechnology and farming.